Borrowing from Adult Cardiac Surgeons—Bringing Congenital Heart Surgery Up to Speed in the Minimally Invasive Era. Issue 2 (March 2020) - Alsarraj, Mohammed K.; Nellis, Joseph R.; Vekstein, Andrew M.; Andersen, Nicholas D.; Turek, Joseph W.
The majority of congenital and adult cardiac surgery is performed through a median sternotomy. For surgeons, this incision provides excellent exposure; however, for patients, a median sternotomy confers a poorer cosmetic outcome and the possibility of postoperative respiratory dysfunction, chronic pain, and deep sternal wound infections. Despite the advances in adult cardiac surgery, the use of minimally invasive techniques in pediatric patients is largely limited to small case series and less complex repairs. In this article, we review the risks, benefits, and limitations of the minimally invasive congenital cardiac approaches being performed today. The interest in these approaches continues to grow as more data supporting reduced morbidity, decreased length of stay, and faster recovery are published. In the future, as the technology and surgical familiarity improve, these alternative approaches will become more common, and may someday become the standard of care.